Bone Marrow Changes Induced by Guiera Senegalensis in Acetic Acid-induced Colitis in Wistar Rats - , S. M. Sahabi; , S. D. Abubakar (Archives of Current Research International, 2018)
Introduction: Inflammatory bowel disease (IBD) comprises Crohn's disease (CD) and ulcerative colitis (UC) which are defined as chronic and relapsing inflammations of the gastrointestinal tract caused by variable pathophysiological mechanisms. Synthetic chemical moieties with antioxidant potential are the present treatment regimens, but their high relapse rate and toxicities limit their utility in treatment. Aims: The aim of this work was to investigate the possible toxic effects that the aqueous extract of Guiera senegalensis will elicit on the bone marrow of experimental animals. Methods: Experimental colitis was induced in animals using acetic acid to mimic human IBD. The effects of oral administration of the extract on the bone marrow were assessed using appropriate tools. A control, colitis control and a treatment control (prednisolone) were used as a guide in the assessment of the findings in this study. Results: Animals receiving the extract showed essentially normal erythroid nests and granulocytic precursors as well as several lymphocytes. Animals receiving prednisolone, on the other hand, showed predominantly granulocytic progenitors with an overall decrease in cellularity of the bone marrow. No toxic effect was observed in bone marrow of animals receiving the extract. Conclusion: The G. senegalensis extract showed no toxicity to the bone marrow and may elicit immunomodulatory properties.